Moralities and power: understanding the moral labour of national aid professionals in Jordan - Ronde, Brigit (Journal of global ethics, 2025)
This article explores the ‘moral labour’ of national aid professionals in Jordan, particularly in their interactions with ‘Northern-led’ humanitarian organisations. It sheds light on the complexities of navigating different moralities within a humanitarian system that is shaped by unequal power relations and ongoing coloniality, highlighting the additional labour that is placed upon national professionals in this context. Building on decolonial studies, the research situates the moral tensions and moral labour within broader historical and structural power dynamics. It thereby illustrates the additional layers of moral labour that national professionals must undertake to navigate and reconcile personal beliefs, professional roles, and different interests, while operating in a system that marginalises their expertise. By focusing on the often-overlooked perspectives and experiences of national aid workers, this study offers new insights into the role of morality in humanitarian aid work and brings attention to the invisible and often unrecognised moral labour integral to aid work. The article underscores the need for a more equitable humanitarian system that values diverse knowledges and moralities, and acknowledges and compensates the moral labour of national professionals.